2007
DOI: 10.1016/j.jacc.2007.04.051
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Stent Thrombosis After Implantation of Sirolimus-Eluting Stents in Diabetic and Nondiabetic Patients

Abstract: The risk of sirolimus stent thrombosis is higher for multiple-vessel disease diabetic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
104
1
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 198 publications
(113 citation statements)
references
References 25 publications
(18 reference statements)
6
104
1
2
Order By: Relevance
“…An explanation may be that patients with type 2 diabetes have higher risk of late complications after coronary interventions than patients without diabetes, including more recurrent myocardial infarctions and target lesion revascularizations (25,26). Half of the recurrent events in patients with CAD in the current study were myocardial infarctions, compared with 10-25% in patients with vascular disease at another location.…”
Section: Discussionmentioning
confidence: 63%
“…An explanation may be that patients with type 2 diabetes have higher risk of late complications after coronary interventions than patients without diabetes, including more recurrent myocardial infarctions and target lesion revascularizations (25,26). Half of the recurrent events in patients with CAD in the current study were myocardial infarctions, compared with 10-25% in patients with vascular disease at another location.…”
Section: Discussionmentioning
confidence: 63%
“…[49][50][51][52] Moreover, Nakazawa et al 45 reported acute ST complicated with MI in 2 patients with RI. Halkin et al 4,53 demonstrated that ST rates were higher after DES than BMS use, regardless of patients' renal function.…”
Section: Des Thrombosismentioning
confidence: 99%
“…The mechanism underlying ST involves multiple factors, so prevention is not very effective. As reported in the literature (Moussa et al, 1999;Cheneau et al, 2003;Buonamici et al, 2007;Machecourt et al, 2007), ST formation is related to many factors such as acute coronary syndrome, plaque rupture, platelet activation, and increased agglutinant release in vivo. In some cases, aspirin and clopidogrel were not fully used and were even discontinued (case 2 in this paper).…”
Section: Discussionmentioning
confidence: 79%